Implementation of Green Recruitment and Green Training Development on Employee’s Environmental Performance at Conrad Bali Hotel - Ni Made Septiawati; I Ketut Astawa; Ni Nyoman Triyuni; I Gusti Agung Bagus Mataram (International Journal of Glocal Tourism, 2022)
Purpose: This article was purposed to analyze the development of existing green recruitment and green training as well as the best approach to take to improve employee environmental performance at the Conrad Bali Hotel. Research methods: Quantitative data analysis was applied in this research using multiple linear regression analysis in the SPSS program, and qualitative descriptive analysis was used to interpret the information in words based on result and the actual situation. Findings: Green recruitment and green training development are the practices of green human resources management used at the hotel. This implementation gives a positive influence on the employee's environmental performance. The hotel's management needs to be concerned about its environmental performance through green recruitment and green training development. Implication: The employees are expected to have a sustainability vision in the end therefore the hotel can improve its environmental performance.